2023
DOI: 10.1039/d3qi00128h
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free catalytic conversion of CO2into methanol: local electrophilicity as a tunable property in the design and performance of aniline-derived aminoborane-based FLPs

Abstract: A deeper computational mechanistic study of a more environmentally friendly metal-free CO2 reduction process towards obtaining methanol is presented, employing a previously tested kind of intramolecular Frustrated Lewis Pair (2-[bis(R)boril]-N,N-dimethylaniline-based)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…Finally, the comparison between the Δ G H 2 ↔ ω B + relationship found in this work with that found in the previous work 33 to see differences when considering a larger set of reactions is discussed in more detail in the ESI †. Thus, it is recommended to use our new relationship between Δ G H 2 and ω B + , which is a more general expression since it takes into account a larger set of systems, being valid for a wide range of ω B + values.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Finally, the comparison between the Δ G H 2 ↔ ω B + relationship found in this work with that found in the previous work 33 to see differences when considering a larger set of reactions is discussed in more detail in the ESI †. Thus, it is recommended to use our new relationship between Δ G H 2 and ω B + , which is a more general expression since it takes into account a larger set of systems, being valid for a wide range of ω B + values.…”
Section: Resultssupporting
confidence: 72%
“…Recently, it has been shown that the local electrophilicity condensed on the boron atom (u B + ) is inversely related to the Gibbs free energy of the H 2 activation using a 2-[bis(R)boryl]-N,Ndimethylaniline-based FLP, 33 i.e., the higher the u B + value, the more exergonic the process is, where u B + was then proposed as a measure of the Lewis acidity of the B atom. Note that in that study, the substitution of the N atom was not varied.…”
Section: Electronic Properties Of Flps and Their Effect On The Revers...mentioning
confidence: 99%
See 1 more Smart Citation
“…(5) Our ASM examinations indicate that the structural deformation energy of CO 2 is the primary factor influencing the activation barrier of the binding reaction between intramolecular geminal M + /G15-based FLP-type molecules and CO 2 . 117 (6) Our study of the CO 2 binding reaction using intramolecular geminal M + /P-based or Zr + /G15-based FLPs demonstrates that the presented computational results are consistent with the Hammond hypothesis, which states that an earlier transition state corresponds to a lower free energy barrier, while a later transition state corresponds to a higher free energy barrier.…”
Section: Discussionsupporting
confidence: 73%
“…(5) Our ASM examinations indicate that the structural deformation energy of CO 2 is the primary factor influencing the activation barrier of the binding reaction between intramolecular geminal M + /G15-based FLP-type molecules and CO 2 . 117…”
Section: Discussionmentioning
confidence: 99%